2001
DOI: 10.1128/jcm.39.9.3204-3212.2001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for Detection, Typing, and Quantification of Human Papillomaviruses in Clinical Samples

Abstract: We report the development of a novel detection and typing methodology for human papillomaviruses (HPV) based on real-time PCR with the self-probing fluorescent primers known as Scorpions. This technique is quick, simple, specific, sensitive, and capable of estimating viral load per cell. We report the results of over 100 typing reactions performed on cell lines, biopsies, and cervical cytobrush samples which, when compared to the current reference HPV detection and typing technique, present a value of 0.89. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
8

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 27 publications
1
28
0
8
Order By: Relevance
“…All of these strategies have advantages and disadvantages, depending on their application (5,10,26). Several consensus PCR systems have been conveniently used in several large-scale epidemiological studies (9,10,19). However, consensus PCR products do not provide practical information for genotyping (26).…”
mentioning
confidence: 99%
“…All of these strategies have advantages and disadvantages, depending on their application (5,10,26). Several consensus PCR systems have been conveniently used in several large-scale epidemiological studies (9,10,19). However, consensus PCR products do not provide practical information for genotyping (26).…”
mentioning
confidence: 99%
“…Recent studies suggest that HPV-16 viral load may be used as a molecular biomarker to improve the prognostic value of HPV testing (8)(9)(10). Other studies found a positive correlation between high HPV-16 load and high-grade squamous intraepithelial lesions (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Many PCR-ELISAs have been developed for the detection, identification, and quantification of a large variety of viruses (2,8,14,23,35,46,47,50,57,62,63,71,75,77,83). In the present study, we have developed and evaluated a PCR-ELISA protocol for the detection and identification of clinically relevant human group A rotavirus G (G1 to G6, G8 to G10, and G12) and P (P [4], P [6], P [8], P [9], and P [14]) genotypes.…”
Section: Discussionmentioning
confidence: 99%